Composição química e potencial antifúngico do óleo essencial de coriandrum sativum contra biofilme e células planctônicas de isolados clínicos de candida albicans - Santos, Antônia Nádia Brito dos (2024)
Fungal infections and microbial resistance are among the biggest global health challenges. In the search for new formulations that minimize and resolve such socioeconomic impacts, science has dedicated itself to the study of medicinal plants, which constitute a source of bioactive substances, many of which are still unknown. Coriander (Coriandrum sativum), belonging to the Apiaceae family, is one of the most consumed vegetables in Brazil. The plant has promising chemical compounds, with recorded antimicrobial activities against a range of bacteria and fungi. In this context, the present study aimed to extract and analyze the essential oil from C. sativum leaves, against clinical strains of C. albicans in planktonic and biofilm form. Furthermore, its cytotoxicity, antioxidant profile, and molecular coupling between C. sativum essential oil compounds (EOCS) and Candida albicans binding proteins were analyzed. The chemical profiles were studied using a Shimadzu Nexis GC 2030 gas chromatograph and flame ionization detector (GC-FID). The antifungal and antibiofilm activities were evaluated using the microdilution assay and crystal violet quantification, respectively. Modulatory activity with amphotericin B was determined using a checkerboard assay. DPPH (2,2-diphenyl-1-picrylhydrazyl), evaluated the antioxidant potential. An initial screening was carried out with Artemia salina L. to evaluate the toxic potential of EOCS. Cytotoxic effects were examined on human red blood cells and Vero cells. To verify the molecular docking, the main compounds of the EOCS with ALS3 and SAP5 proteins were used. The phytochemical profile demonstrated compounds rich in alcohols and aldehydes, with decanal being the most expressive. The Minimum Inhibitory Concentration (MIC) and Minimum Fungicide Concentration (MFC) of EOCS against the tested strains range from 625 to 2,500 μg/ml. EOCS showed an anti-adhesion effect on the C. albicans biofilm, where the compound was able to inhibit the biofilm biomass of ATCC 90028 by 80% at a concentration of 2XMIC and a 77% reduction for the clinical isolate strain. The study provides promising data where EOCS presents fungicidal activities against C. albicans in its planktonic and biofilm form. The assay with A. salina showed high toxicity, however, EOCS showed low toxicity in hemolysis and cytotoxicity assays with VERO cells. Interactions with ALS3 and SAP5 showed that the binding site of the compounds on proteins is different from amphotericin B. These results highlight the antifungal potential of EO from C. sativum leaves and suggest ways for the development of new antimicrobials.